Engineering design - Dieter, George E., 1928-; Schmidt, Linda C. (McGraw-Hill, 2013)
Dieter's Engineering Design represents a major update of this classic textbook for senior design courses. As in previous editions, Engineering Design provides a broader overview of topics than most design texts and contains much more prescriptive guidance on how to carry out design. Dieter focuses on material selection as well as how to implement the design process. Engineering Design provides the senior mechanical engineering students with a realistic understanding of the design process. It is written from the viewpoint that design is the central activity of the engineering profession, and it is more concerned with developing attitudes and approaches than in presenting design techniques and tools -- Publisher's description.